Building Maritime Domain Awareness as an Essential Element of the Global Maritime Fulcrum: Challenges and Prospects for Indonesia’s Maritime Security - Agastia, I Gusti Bagus Dharma; Perwita, Anak Agung Banyu (Universitas Muhammadiyah Yogyakarta, 2017)
The Global Maritime Fulcrum has been an essential cornerstone of Indonesian foreign and domestic policy for the Joko Widodo administration. It envisions Indonesia as a regional maritime power capable of providing maritime security within its territorial waters and within the Indo-Pacific region. It also captures Indonesia’s ambition to boost its maritime economy. The Joko Widodo administration has been building the Global Maritime Fulcrum for three years. Though physical development has indeed been remarkable, there has been a lack of a focus on developing maritime domain awareness, or MDA. As an essential foundation of maritime policy, it is important that a state invests in ensuring adequate MDA-building capacities to guide its maritime policy. Without proper MDA, it would be difficult for maritime stakeholders to allocate and prioritise maritime resources to the key areas of concern of the Global Maritime Fulcrum.This paper constructs a framework of MDA, which is used to examine the issues with Indonesia’s MDA-building process at three levels: strategic, operational, and technical. It identifies three issues, namely a lack of capacity to conduct sustained MDA operations, a lack of inter-agency coordination, and the problem of maritime ‘sense-making’. Several policy recommendations aimed at increasing Indonesia’s capacity to build MDA are proposed at the end.